Tax Socialization for MSMEs to Encourage People to be Tax Aware in Caturtunggal Village - Anisa; Eni Nugraeni (Jurnal Pengabdian Masyarakat Bestari, 2024)
Two (MSMEs) located in Caturtungaal Village, Depok District, Sleman Regency, partnered in this community service to increase public understanding of the Final Income Tax. Observation, training, evaluation, and counseling are the techniques used. The reason for choosing MSMEs is due to a lack of understanding of taxation. According to the plan, the activity is carried out in stages by visiting partners one by one at their workplaces. The results showed that the target partners gained a better understanding of taxation, MSME Final Income Tax, how to calculate MSME Final Income Tax, and how to make an NPWP.